A BLUE-PRINT FOR PERFORMING PAEDIATRIC PHARMACOLOGICAL RESEARCH. Issue 1 (14th December 2015) - Vermeulen, Eric; Nuytemans, Debbie; de Haan, Timo; Flint, Robert; der Lee, Johanna van
Abstract : Introduction: In order to develop rational, patient tailored dosing schemes, population PK/PD studies in children and infants are needed. The emergence of new laboratory techniques (LC-MS/MS) and statistical tools (population PK/PD modeling) allows for the analysis of sparse and unbalanced data and has increased the possibilities to perform (observational) PK/PD studies in the paediatric clinic. To improve the quality of future pediatric PK/PD investigations the experience and knowledge about these tools should be shared and a basic study template agreed upon. Objective: We aim to present a possible blue-print to assist paediatricians in the design and conduct of multicentre PK/PD studies in children and infants. Methods: Based on a review of the existing literature and multiple interviews with paediatricians and pharmacologists involved in multicenter paediatric PK/PD research a blue-print is drafted containing recommendations and examples for the design and implementation of PK/PD studies in children. The draft blue-print will be available at the conference and participants are asked for feed-back. Results: PK/PD research to determine dosing in children and infants is preferably performed in a multi-center infrastructure in order to include a sufficient number of subjects within a reasonable time, covering all covariates relevant for dosage. The multi-center collaboration may also enable the analysis of multiple drugs in one cohort increasing cost-efficiency. Formal monitoring is needed to guarantee the quality of collected data. Discussion: If performed well, the results of these studies will contribute to the evidence base underlying clinical guidelines and regulatory decisions concerning labeling adjustments.